High insertion of the right diaphragm complicated with congenital diaphragmatic hernia: A case report of rare thoracoscopic findings. Issue 4 (20th June 2022) - Ishimoto, Kenta; Hayashida, Makoto; Ueda, Michiko; Okamura, Kaori; Ieiri, Satoshi
Abstract: We encountered a case of high insertion of the right diaphragm complicated with congenital diaphragmatic hernia that was diagnosed based on thoracoscopic findings. A full‐term male baby was suspected of having right congenital diaphragmatic hernia or diaphragmatic eventration on postnatal imaging. He only had episodes of mild but prolonged symptoms following upper respiratory tract infection and his course was otherwise uneventful during outpatient monitoring. At 1 year old, the elevated liver volume remained large, which might eventually interfere with his lung growth, so thoracoscopic exploration was planned. Thoracoscopy revealed liver prolapse from a diaphragmatic defect. In addition, the anterior to lateral inserted part of the diaphragm was high, with the anterior part reaching the fourth rib. We repaired only the diaphragmatic defect without repositioning the diaphragm, and the postoperative course was uneventful. High insertion of the diaphragm should be considered as a differential diagnosis of congenital diaphragmatic eventration.